Вынужденные колебания трубопроводов гидросистемы копрового пресса - Астахова, К. В.; Жовдак, В. А.; Татьков, В. В.; Трубаев, Александр Иванович; Федоренко, И. М. (НТУ "ХПИ", 2006)
On the basis of a finite element method the numerical researches of forced and free vibrations and strength of the pipeline of a hydraulic-circuit system were under an operation of transient shocks are held. The estimation of influence of internal pressure on a spectrum of natural frequencies and stress state of a system is given. The dynamic responses of internal pressure are defined experimentally
Keywords: вынужденные колебания; пульсация давления в коллекторе; металлический лом; вторичное сырье